The Declarations and Promises Made in Mixed Marriages: Procedural Acts for Legislation - Suma, I Made Markus (2020)
The Church safeguards the rights of her members through enormous canonical provisions, not excluding the right to marry (ius connubii). The right to marry is the freedom of each Christ’s faithful to choose a person to become his or her husband or wife in living out the partnership of one’s whole life (totius vitae consortium), including in entering into mixed marriages. The marriage of at least one party who is a Catholic, however, is governed not only by divine law but also by canon law. The making of declaration to be faithful to the Catholic faith and a sincere promise to have all children baptized in the Catholic Church to be made by the Catholic party are required by canon 1125. In fact, it is left to the authority of the Bishops’ Conference to determine the manner of the making of declarations and promises ad normam canon 1126. With respect to the legislative power endowed by universal law to the Bishops’ Conference, this research is an attempt to offer procedural acts to be legislated by the said ecclesiastical authority.
Keywords: Eheschließung; Mischehe; Verlöbnis; Bischofskonferenz